Сучасний стан та перспектви розвитку біржового товарного ринку України - Завадських, Ганна Миколаївна; Завадских, Анна Николаевна; Zavadskykh, Hanna; Тебенко, Віта Миколаївна; Тебенко, Вита Николаевна; Tebenko, Vita (My University, 2018)
UK: Дослідження присвячено питанням стану та подальшого розвитку біржового товарного ринку в Україні. Визначено сучасні тенденції розвитку вітчизняного біржового ринку. Наведено основні причини неефективного функціонування біржового ринку України. Розглянуто проблеми і перешкоди в розвитку біржової торгівлі в Україні. Визначено перспективи його подальшого розвитку. EN: The stock commodity market in Ukraine is only being formed. At the present stage of development, it practically does not perform any of the functions inherent in this market structure. The need to study the current state of the stock commodity market in Ukraine and determine the prospects for its further development is due. an extremely important role of stock exchange activity in the financial and economic system of the country It is determined that the legal framework regulating stock exchange activities is imperfect and unprotected. In Ukraine, by this time, there is no single classification of goods, as a result of which in the structure of stock exchange there are so-called non-commodity goods. A significant feature of the Ukrainian stock market is the large number of exchanges, almost half of which do not work. At the current stage, stock exchange activity in Ukraine is characterized by low efficiency. The dynamics of the number of trades and the value of concluded deals over the past 7 years has a tendency to decrease. The stock market is negatively affected by the economic crisis, the unstable political situation and military actions in the East. A small amount of operations in the commodity market is due to its low liquidity, which, in turn, hold back its development. The analysis showed that agricultural commodity prevails in the commodity structure of stock exchange. For commodity exchanges in Ukraine characterized volatility of prices - significant fluctuations in prices during the trading session. Exchange trading in Ukraine is represented mainly by the spot market, ie the conclusion of transactions for real goods with immediate delivery. With all the diversity of financial instruments, including derivatives, only derivatives are used in Ukraine.
Current state and prospects for development of the stock commodity market of Ukraine
Keywords: біржовий ринок; біржа; біржова діяльність; біржова торгівля; товарна біржа; фондова біржа; біржова угода; біржовий товар; котирування; біржові торги; stock market; stock exchange; stock exchange activities; stock trading; commodity exchange; agricultural exchange; stock exchange transactions; commodity stock; quotes